Madrasah Ibtidaiyah Teacher Candidates' Strategies in Fostering Student Discipline in the Digital Age - Samiha, Yulia Tri; Fauzi, Muhammad (Journal of Educational Sciences, 2025)
The development of technology in the digital era brings its own challenges in the world of education, especially in maintaining and fostering student discipline. Madrasah Ibtidaiyah (MI) as an Islamic-based basic education institution needs to have adaptive strategies that are in accordance with the characteristics of the times and still uphold moral values. This study aims to examine the strategies used by MI teacher candidates in fostering student discipline in the digital era. The method used is descriptive qualitative research with a thematic analysis approach. The research subjects consisted of 40 final students of the PGMI Study Program at UIN Raden Fatah Palembang who had taken teaching practice. Data were collected through an open-ended questionnaire and analyzed using NVivo 14 software. The results showed that prospective teachers' understanding of discipline focuses on compliance with rules as a form of responsibility and self-control. The strategies identified include communicative approaches, giving rewards, and applying consequences for violations. The authoritative approach is the dominant strategy, as it combines the firmness of rules with emotional support. The best practice in instilling discipline is the teacher's exemplary behavior that is consistently displayed, making the teacher a role model in shaping students' character. This study concludes that the strategy of MI teacher candidates in building student discipline must combine technological aspects, humanist approaches, and Islamic character values to answer the challenges of education in the digital era.